THE URGENCY OF MICRO TEACHING PROGRAM IN MODERN ISLAMIC BOARDING SCHOOLS - Lahat, Mohammad Amas; Ma’ruf, Ammar; Tazali, Imam (LP2M IAI Al-Khairat Pamekasan, 2025)
This research aims to determine the activeness of learning for each subject, using a micro-teaching program aimed at the abilities of teachers in Modern Islamic Boarding Schools. The research results show that the implementation of the micro-teaching program for teachers at Modern Islamic Boarding Schools is based on planning and micro-teaching guidelines. This is to increase the competency of students in the learning process as well as increase the competency of students in understanding the material contained in each core discussion, teacher preparation, class preparation, steps in student learning activities, and learning evaluation. Increasing the ability of language teachers means developing a spirit of love for teachers for language.